Regional Economic Outlook, October 2010, Middle East and Central Asia. (Regional Economic Outlook, 2010)
The Regional Economic Outlook assesses the near-term outlook for each of the three subregions: the Middle East, North Africa, Afghanistan, and Pakistan (MENAP) oil exporters, the MENAP oil importers, and the Caucasus and Central Asia (CCA). The report also looks at medium-term issues of particular concern to the region, namely the need to boost competitiveness and growth to address high levels of long-standing unemployment in the MENAP region, and enhance the effectiveness of monetary policy and regional cooperation in the CCA.